Exploring multivalued probabilistic ψ-contractions with orbits in b-Menger spaces - Achtoun, Youssef; Radenović , Stojan; Tahiri, Ismail; Lamarti Sefian, Mohammed (Vojnotehnički glasnik / Military Technical Courier, 2024)
Introduction/purpose: The paper presents a novel approach to certain well-established fixed point theorems for multivalued probabilistic con- tractions in b-Menger spaces, leveraging the boundedness of the orbits. The aim was to generalize and enhance the results previously derived by Fang and Hadžić. Methods: The boundedness of orbits in b-Menger spaces is used to establish their approach for multivalued probabilistic contractions. Results: The findings of the study not only generalized the existing fixed point theorems but also enhanced them significantly. The effectiveness of the approach in extending the results originally proposed by Fang and Hadžić was showcased. Moreover, the applicability of the coincidence fixed point theorem in fuzzy b-metric spaces was demonstrated. Conclusions: The study presented a novel perspective on fixed point the- orems in multivalued probabilistic contractions within b-Menger spaces. By leveraging boundedness and introducing a coincidence fixed point theorem for fuzzy b-metric spaces, the work contributed to the advance- ment in this field.